Importance and Acceptance of Ecuadorian Cocoa in the European Union Market - González-Vásquez, Mónica de Los Ángeles; Ramírez-Blacio, Anita Maribel; Contreras-Peña, María Fernanda; Cevallos-Castro, Delia Alexandra; Sambonino-García, Bárbara de Lourdes; Poveda-Burgos, Guido Homero; Vera-Garzón, Omar Casenelly (Journal of Ecohumanism, 2025)
A systematic review was carried out on the production and publication of research papers related to the study of Exports, Cocoa and the European Union under the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) approach. The purpose of the analysis proposed in this document was to know the main characteristics of the publications registered in the Scopus and Wos databases during the study of the proposed variables, achieving the identification of 28 publications in total. Thanks to this first identification, it was possible to refine the results through the keywords entered in the search button of both platforms, which were EXPORT, AND COCOA, AND EUROPEAN AND UNION, reaching a total of 11 documents, excluding duplicates and those that did not meet the analysis criteria.